Bottom-up fabrication of 2D Rydberg exciton arrays in cuprous oxide - Kinjol Barua; Samuel Peana; Arya Deepak Keni; Vahagn Mkhitaryan; Vladimir M. Shalaev; Yong P. Chen; Alexandra Boltasseva; Hadiseh Alaeian (Communications Materials)
Abstract Solid-state platforms provide exceptional opportunities for advancing on-chip quantum technologies by enhancing interaction strengths through coupling, scalability, and robustness. Cuprous oxide (Cu2O) has recently emerged as a promising medium for scalable quantum technology due to its high-lying Rydberg excitonic states, akin to those in hydrogen atoms. To harness these nonlinearities for quantum applications, the confinement dimensions must match the Rydberg blockade size, which can reach several microns in Cu2O. Using a CMOS-compatible growth technique, this study demonstrates the bottom-up fabrication of site-selective arrays of Cu2O microparticles. We observed Rydberg excitons up to the principal quantum number n = 5 within these Cu2O arrays on a quartz substrate and analyzed the spatial variation of their spectrum across the array, showing robustness and reproducibility on a large chip. These results lay the groundwork for the deterministic growth of Cu2O around photonic structures, enabling substantial light-matter interaction on integrated photonic platforms and paving the way for scalable, on-chip quantum devices.